Pemberdayaan kelompok tani tambak garam bulcin mandiri di Desa Bulu Cindea Kecamatan Bungoro Kabupaten Pangkep - Abd. Rasyid Jalil; Rahmi Rahmi; Abdul Rakhim Nanda; Rahmat Muhammad; Ilham Jaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The development of Bulu Cindea village’s potential, especially salt in Pangkep Regency, needs to be continuously pursued to improve farming community’s economy, especially salt. This service program aims to produce iodized salt consumption by innovating consumption salt equipment to increase salt production and productivity at a low cost and sustainable manner. Through FGDs and technical guidance on the utilization of low power equipment, by metthos used was following with the salt farmer group’s household electricity capacity. This service activity will benefits various parties, including village community groups involved in community service, universities, and village government officials. The target audience for this service activity is the group of salt farmers in Bulu Cindea village. After this service activity was carried out, there was a change in behaviour through the understanding of the partner group about the better quality of consumption salt. The post-test results showed that the groups understanding of the activity participants reached 82.5%.The need for further community empowerment in building an iodized salt processing industry improves public welfare and health.